Clinical efficacy and acceptability of remote fetal heart rate self-monitoring in Southern China - Gan, Yujie; Zhu, Caixia; Zhou, Yueqin; Wu, Jieying; Cai, Fenge; Wu, Qiang; Huang, Jingwan; Zhu, Yanna; Chen, Haitian (BMC pregnancy and childbirth, 2023)
BackgroundCompared to traditional fetal heart rate monitoring (FHR) for the outpatients in clinic, remote FHR monitoring shows real-time assessment of fetal wellbeing at home. The clinical function of remote FHR monitoring in pregnant wome in outpatient is still unclear.ObjectiveTo explore the feasibility of remote FHR self-monitoring in singleton pregnant women from southern China.Study designThis prospective cohort study was conducted at one tertiary center in southern China. Pregnant women used a mobile cardiotocogram device to measure the FHR at least once a week until delivery in the remote group. For the control group, pregnant women underwent traditional FHR monitoring once a week in the outpatient clinic. The rate of cesarean section, risk of postpartum hemorrhage and adverse neonatal outcomes were compared between the two groups. All the pregnant women completed a questionnaire survey to evaluate their acquisition of remote FHR self-monitoring.ResultsApproximately 500 women were recruited in the remote FHR self-monitoring group (remote group), and 567 women were recruited in the traditional FHR monitoring group (control group). The women in the remote FHR monitoring group were more likely to be nulliparous (P < 0.001), more likely to have a higher education level (P < 0.001) and more likely to be at high risk (P = 0.003). There was no significant difference in the risk of cesarean section (P = 0.068) or postpartum hemorrhage (P = 0.836) between the two groups. No difference in fetal complications was observed across groups, with the exception of the incidence of NICU stays, which was higher in the remote group (12.0% vs. 8.3%, P = 0.044). The questionnaire survey showed that the interval time (P = 0.001) and cost (P = 0.010) of fetal heart rate monitoring were lower in the remote group. Regarding age, prepregnancy BMI, risk factors, education level, maternal risk and household income, senior high school (OR 2.86, 95% CI 1.67–4.90, P < 0.001), undergraduate (OR 2.96, 95% CI 1.73–5.06, P < 0.001), advanced maternal age (OR 1.42, 95% CI 1.07–1.89, P = 0.015) and high-risk pregnancy (OR 1.61, 95% CI 1.11–2.35, P = 0.013) were independent factors for pregnant women to choose remote fetal monitoring. Multiparty (OR 0.33, 95% CI 0.21–0.51, P < 0.001), full-time motherhood (OR 0.47, 95% CI 0.33–0.678, P < 0.001) and high household income (OR 0.67, 95% CI 0.50–0.88, P = 0.004) were negatively correlated with the choice of remote FHR self-monitoring.ConclusionRemote FHR self-monitoring technology has a lower cost and shows potential clinical efficacy for the outpatient setting in southern China. This approach does not increase the risk of cesarean section or adverse neonatal outcomes. It is acceptable among nulliparous pregnant women with a high education level, high household income or high risk. Further research is needed to assess the impact of this technology on obstetric outcomes in different health settings.